2013
DOI: 10.1159/000343400
|View full text |Cite
|
Sign up to set email alerts
|

Calf Bioimpedance Spectroscopy for Determination of Dry Weight in Hemodialysis Patients: Effects on Hypertension and Left Ventricular Hypertrophy

Abstract: Background/Aims: Dry weight estimation in hemodialysis patients is still a substantial problem. Despite meticulous clinical assessment, fluid overload is common, leading to hypertension and left ventricular hypertrophy (LVH). Segmental calf bioimpedance spectroscopy (cBIS) is a novel tool for dry weight assessment. Here we tested the hypothesis, that its clinical routine use reduces arterial hypertension and left ventricular mass. Methods: Left ventricular mass (determined by magnetic resonance imaging), blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Furthermore, a recent study during a 6-month follow-up further supports the presumption of positive effect of volume control in dialysis patients using clinical routine by segmental calf bioimpedance spectroscopy (cBIS) for dry weight assessment. Also, myocardial mass and LVMi dropped constantly in that study [20].…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, a recent study during a 6-month follow-up further supports the presumption of positive effect of volume control in dialysis patients using clinical routine by segmental calf bioimpedance spectroscopy (cBIS) for dry weight assessment. Also, myocardial mass and LVMi dropped constantly in that study [20].…”
Section: Discussionmentioning
confidence: 57%
“…Although, hemodialysis procedure ameliorate clinical outcomes and survival in uremic patients, chronic exposure to hemodialysis seems to induce changes in HRV [94]. In addition autonomic neuropathy induce alterations in HRV and there is evidence that high fluid overload met in hemodialysis patients also impairs ANS activity, leads to hypertension and left ventricular hyperthrophy where enhances cardiac mortality [95]. It has been found that during the ultrafiltration procedure of the hemodialysis therapy an acute decrease in parasympathetic function and a relative hyperactivity of sympathetic nervous system takes place [96].…”
Section: Discussion-conclusionmentioning
confidence: 99%
“…Systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate were measured in triplicate using a calibrated electronic blood pressure device (Dinamap ProCare, General Electric Healthcare, Munich, Germany, cuff sizes according to upper arm circumference, size 1: 198 27-35 cm, size 2: 34-43 cm). Electrode positions and resistivity measurements were carried out as described before [6,7,9] by one out of 2 trained investigators (S.G.M. and J.P.).…”
Section: Study Protocolmentioning
confidence: 99%
“…In recent years, bioimpedance analysis has gained more attention and different approaches have been developed to address fluid management in HD patients (reviewed in [4] ). We reported earlier on calf bioimpedance spectroscopy (cBIS) as a means for accurately determining DW (cBIS-DW) [5][6][7][8] and were able to demonstrate beneficial effects on left ventricular hypertrophy and antihypertensive medication needs [9] . cBIS does not require comparison of volumes (e.g., extracellular volume, ECV) to a normal population and is based on the flattening of the resistance curve of a segment of the calf that is continuously recorded during HD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation